2015
DOI: 10.1007/s10763-014-9601-6
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of Number Sense in Pre-service Secondary Mathematics Teachers

Abstract: This paper presents some results of an investigation on the number sense of a group of pre-service secondary teachers from Spain. The objective of this research was to analyze students' use of strategies associated to number sense and compare them with those obtained in a previous study with pre-service primary teachers in Taiwan, ( Yang, Reys & Reys, International Journal of Science and Mathematics Education, 7, 383-403, 2009). Pre-service secondary teachers showed lower success than pre-service primary teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…In addition, the reason why Syrian immigrant students preferred number sense-based solutions more than other solutions in WTTT-NS is one of the surprising results of this study, and it should be noted that most students have a low level of number sense. Compared to these results, a number of studies (Almeida et al, 2016;Kayhan Altay, 2010;Yapici, 2013) have found that rule-based solutions are preferred due to rote-learning, while Caglar (2021) and Chen et al (2015) have reported that misconception-based solutions are predominant in their studies. However, the fact that Caglar (2021) and Yang and Cheung (2020) stated that number sense-based solutions are dominant in the component of recognizing the relative number size in their studies, being similar to the results obtained in the current study.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 94%
“…In addition, the reason why Syrian immigrant students preferred number sense-based solutions more than other solutions in WTTT-NS is one of the surprising results of this study, and it should be noted that most students have a low level of number sense. Compared to these results, a number of studies (Almeida et al, 2016;Kayhan Altay, 2010;Yapici, 2013) have found that rule-based solutions are preferred due to rote-learning, while Caglar (2021) and Chen et al (2015) have reported that misconception-based solutions are predominant in their studies. However, the fact that Caglar (2021) and Yang and Cheung (2020) stated that number sense-based solutions are dominant in the component of recognizing the relative number size in their studies, being similar to the results obtained in the current study.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 94%
“…To select the students a written test was given to two groups of forty-seven eighth graders. The test contained items associated with the three number sense components described earlier (Bruno y Perdomo-Díaz, 2014, 2016. Based on the results of the test, the eleven students were selected.…”
Section: Samplementioning
confidence: 99%
“…The researchers who have evaluated number sense in students from both educational stages have concluded that most students tend to use rules and algorithms when solving number problems (Veloo, 2010;Yang, 2005;Yang et al, 2008). Inadequate number sense skills have also been found in research involving in-service and pre-service primary and secondary school teachers, which highlights the need to address this deficiency as part of their university (Veloo, 2010;Almeida, Bruno y Perdomo-Díaz, 2014, 2016Tsao, 2004;Sengul, 2013;Yang, Reys, & Reys, 2009). These findings have serious implications for classroom instruction, especially if we consider that a limited knowledge of a subject restricts teachers' ability to promote conceptual learning in their students.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers who have evaluated number sense in students from both educational stages have concluded that most students tend to use rules and algorithms when solving number problems (Veloo, 2010;Yang, 2005;Yang et al, 2008). Inadequate number sense skills have also been found in research involving in-service and pre-service primary and secondary school teachers, which highlights the need to address this deficiency as part of their university (Veloo, 2010;Almeida, Bruno y Perdomo-Díaz, 2014, 2016Tsao, 2004;Sengul, 2013;Yang, Reys, & Reys, 2009). These findings have serious implications for classroom instruction, especially if we consider that a limited knowledge of a subject restricts teachers' ability to promote conceptual learning in their students.…”
Section: Components Of Number Sensementioning
confidence: 99%
“…Sowder (1992) noted that the lack of an operational definition of number sense is a significant impediment to its evaluation, which is why various components have been used to characterize it. Proposals for said characterization have been put forth using different numbers of components, all of them being grouped or divided depending on their practicality to the research (McIntosh et al, 1992;Reys & Yang, 1998;Almeida, Bruno y Perdomo-Díaz, 2014, 2016Berch, 2005;Methe et al, 2001;NCTM, 2000). Table 1 shows a component description, framework of our research, which considers the components of the different proposals made to date.…”
Section: Introductionmentioning
confidence: 99%